Legal Policy Model of the Red and White Village Cooperative (KDMP): Implementation Factors and Comparative Insights from Brazil, Denmark, and Japan - Mauludin, Novie Afif; Wahyudi, Ary; Ulum, Hafizatul (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
This study examines the legal policy model of the Red and White Village Cooperative (KDMP), the determinants of its implementation, and Indonesia’s comparative position vis-à-vis cooperative systems in Brazil, Denmark, and Japan. The urgency of this research stems from the Indonesian government’s large-scale initiative to establish and revitalize more than 80,000 village cooperatives through a centralized, top-down regulatory framework, implemented amid persistent structural challenges, including regulatory ambiguity, limited managerial and digital capacity, uneven infrastructure, and variations in community participation. Without careful legal policy evaluation, this model risks reproducing structural weaknesses previously observed in Indonesia’s Village Unit Cooperatives (KUD). Employing a normative–empirical legal methodology that integrates statutory analysis, conceptual inquiry, comparative law, and a sociological approach supported by interviews and field-based questionnaires in selected villages in West Nusa Tenggara, the study finds that KDMP’s legal policy is predominantly shaped by Thomas R. Dye’s institutional and process models. This centralized framework enables rapid nationwide implementation but reveals a structural misalignment between legal design and practical readiness at the village level. Implementation outcomes are influenced by both juridical factorsparticularly regulatory clarity and policy coherence and non-juridical factors, including human resources, digital infrastructure, and levels of member participation. A comparative analysis based on Ragone and Smorto’s functional framework demonstrates that, while Indonesia shares normative cooperative objectives with Brazil, Denmark, and Japan, differences in governance structures significantly affect sustainability outcomes. Brazil and Denmark illustrate the advantages of autonomy-based, bottom-up cooperative models operating under flexible legal regimes. At the same time, Japan represents a hybrid trajectory in which early state coordination gradually transitions toward member-centered governance. This study contributes an integrated legal-policy model of KDMP that connects implementation realities with comparative insights. The findings indicate that strengthening member-based governance, simplifying overlapping regulations, and gradually reducing excessive centralization are essential to enhance sustainability, community ownership, and the long-term effectiveness of village-based cooperatives in Indonesia. Journal keywords: Legal Policy Model, Comparative Law, and Merah Putih Village Cooperative